Environment changes during Middle to Upper Palaeolithic transition in southern Poland (Central Europe). A multiproxy approach for the MIS 3 sequence of Koziarnia Cave (Kraków-Częstochowa Upland). (February 2021) - Berto, Claudio; Krajcarz, Maciej T.; Hoyo, Magdalena Moskal-del; Komar, Maryna; Sinet-Mathiot, Virginie; Zarzecka-Szubińska, Katarzyna; Krajcarz, Magdalena; Szymanek, Marcin; Wertz, Krzysztof; Marciszak, Adrian; Mętrak, Monika; Suska-Malawska, Małgorzata; et al.
Highlights: A multiproxy approach was applied for palaeoenvironment analyses in Koziarnia Cave. Layers related to Middle Palaeolithic, Jerzmanowician, and Early Gravettian were analysed. Two MIS 3 climate oscillations were detected. Jerzmanowician occupation was connected with a relatively cold episode. Middle Palaeolithic and Early Gravettian groups inhabited the cave during milder climatic conditions. Abstract: Marine Isotope Stage 3 is considered a period with several climate oscillations that drove the environments to rapid changes. To understand how these stadial-interstadial cycles affected southern Poland, we combined the results of eight proxies analysed in the samples from the old excavations and a new 2017 trench of Koziarnia Cave (Ojców National Park, Kraków-Częstochowa Upland, Poland) in layers related to Middle Palaeolithic, Jerzmanowician, and Early Gravettian. Among the studied proxies were charcoals, pollen record, remains of malacofauna, and vertebrates (including rodents, birds and large mammals, and ZooMS analysis of fragmented bones). Moreover, sediment samples have been analysed for lipid composition (by Gas Chromatography-Mass Spectrometry, GC–MS). Despite several taphonomic issues, it was possible to recognise two oscillations. The first one, reflected in pollen record and lipid analysis, took place during Dansgaard-Oeschger (DO) 14 to 8 and included Heinrich Stadial (HS) 4. The second one, recorded by rodents and bird proxies, was related to DO 8/7 to DO 6 and included HS 3. Charcoal and large mammal proxies provided the broad context of our study. The Jerzmanowician occupation was connected with a relatively cold episode in a landscape characterized mainly by grassland and periglacial environments, while the Late Middle Palaeolithic and Early Gravettian groups settled the cave during milder climatic conditions, where environments were open with sparse boreal woodlands. Such trends provide additional arguments in a broad discussion on Middle-Upper Palaeolithic transition in Central Europe.